Network + guide networks - Dean, Tamara (Cengage Learning, 2009)
This book is good for someone who has little experience and wants to learn about the various aspects of networking, or maybe for someone who has experience and needs a refresher on broad based concepts. But despite the book's title, Network+ Guide to Networks should NOT be your one-stop shop if you are looking to pass the Network+ exam.